2022
DOI: 10.1111/gcb.16294
|View full text |Cite
|
Sign up to set email alerts
|

Global evaluation of inhibitor impacts on ammonia and nitrous oxide emissions from agricultural soils: A meta‐analysis

Abstract: Inhibitors are widely considered an efficient tool for reducing nitrogen (N) loss and improving N use efficiency, but their effectiveness is highly variable across agroecosystems. In this study, we synthesized 182 studies (222 sites) worldwide to evaluate the impacts of inhibitors (urease inhibitors [UI], nitrification inhibitors [NI] and combined inhibitors) on crop yields and gaseous N loss (ammonia [NH3] and nitrous oxide [N2O] emissions) and explored their responses to different management and environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 142 publications
1
31
0
Order By: Relevance
“…The performance of CUNI for increasing NUE was more consistent than CU in this study ( Table 1 ). This was probably owing to the effective reduction in N 2 O without triggering the tradeoff between NH 3 and N 2 O emissions, as the N fertilizers were less susceptible to NH 3 losses when incorporated into soil [ 35 ]. Contrary to previously reported findings by Suter et al [ 46 ], the EENF treatments (except for CUNI in 2018) did not further improve the NUE of lettuce system compared to OPT ( Table 1 ), which was probably due to the limited capacity of EENFs for promoting N uptake in this study ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of CUNI for increasing NUE was more consistent than CU in this study ( Table 1 ). This was probably owing to the effective reduction in N 2 O without triggering the tradeoff between NH 3 and N 2 O emissions, as the N fertilizers were less susceptible to NH 3 losses when incorporated into soil [ 35 ]. Contrary to previously reported findings by Suter et al [ 46 ], the EENF treatments (except for CUNI in 2018) did not further improve the NUE of lettuce system compared to OPT ( Table 1 ), which was probably due to the limited capacity of EENFs for promoting N uptake in this study ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous meta-analyses reported that the CRFs and nitrification inhibitors (NIs) could significantly reduce the soil N 2 O emissions by 19–74% and 33–58%, respectively [ 32 , 33 ]. Additionally, the surplus N in soil is found to directly impact the EENF effectiveness, and EENFs provide a greater opportunity for reducing fertilizer N inputs and N 2 O losses in high-N-surplus cropping systems [ 34 , 35 ]. Therefore, it is critical to establish an optimal EENF application strategy specifically targeting the Chinese open-field vegetable systems.…”
Section: Introductionmentioning
confidence: 99%
“…The specific products demonstrated to have such efficacy are nitrification inhibitors and polymer coatings applied to urea. Across a wide range of soils and cropping systems globally, measured nitrous oxide emission reductions averaged 49% for nitrification inhibitors (from 422 observations), 31% for combined urease and nitrification inhibitors (from 118 observations), and 19% for polymer-coated urea (from 89 comparisons) (Fan et al, 2022;Thapa et al, 2016). These reductions in nitrous oxide emissions are larger than the reported effects of these products on crop yield or NUE (7.5 and 12.9%, respectively;Abalos et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The specific products demonstrated to have such efficacy are nitrification inhibitors and polymer coatings applied to urea. Across a wide range of soils and cropping systems globally, measured nitrous oxide emission reductions averaged 49% for nitrification inhibitors (from 422 observations), 31% for combined urease and nitrification inhibitors (from 118 observations), and 19% for polymer‐coated urea (from 89 comparisons) (Fan et al., 2022; Thapa et al., 2016). These reductions in nitrous oxide emissions are larger than the reported effects of these products on crop yield or NUE (7.5 and 12.9%, respectively; Abalos et al., 2014).…”
Section: Reducing Emissions By Reducing Nitrogen Surplusmentioning
confidence: 99%